EMOTIONAL INTELLIGENCE PADA STRESS AKADEMIK MAHASISWA: SYSTEMATIC LITERATURE REVIEW: Sistematik Literature Review - Zaatul Izzah (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
ABSTRACT Academic stress is one of the psychological problems frequently experienced by university students due to various academic demands, including assignments, examinations, academic achievement expectations, and time management challenges. This condition may negatively affect students’ psychological well-being and academic performance. One of the internal factors that can help reduce academic stress is emotional intelligence, which refers to an individual’s ability to recognize, understand, regulate, and express emotions effectively. This study aims to analyze the influence of emotional intelligence on academic stress among university students through a Systematic Literature Review (SLR) approach. Data were collected from relevant scientific articles published in reputable academic databases. The review process involved identification, selection, evaluation, and synthesis of studies that met the inclusion criteria. The findings indicate that emotional intelligence is negatively associated with academic stress. Students with higher emotional intelligence tend to manage academic pressures more effectively, regulate their emotions, adapt to learning challenges, and employ more effective coping strategies, resulting in lower levels of academic stress. Therefore, emotional intelligence is an important factor in supporting students’ ability to cope with academic demands and maintain their psychological well-being. ABSTRAK Stress akademik merupakan permasalahan psikologis yang sering dialami oleh mahasiswa akibat berbagai tuntutan akademik seperti tugas kuliah, ujian, tekanan untuk memperoleh nilai yang baik, serta kemampuan mengatur waktu. Kondisi tersebut dapat memengaruhi kesejahteraan psikologis dan prestasi akademik mahasiswa. Salah satu faktor internal yang diduga berperan dalam mengelola tekanan akademik adalah kecerdasan emosional. Kecerdasan emosional merupakan kemampuan individu untuk mengenali, memahami, dan mengelola emosi diri sendiri maupun orang lain secara efektif. Kajian ini bertujuan untuk mengetahui pengaruh kecerdasan emosional terhadap tingkat stress akademik pada mahasiswa di perguruan tinggi. Metode yang digunakan adalah kajian Systematic Literature Review dengan pengumpulan data melalui sumber-sumber relevan. Selain itu SLR juga bertujuan untuk mengungkapkan teori yang relevan dengan kasus dalam penelitian tersebut.Hasil kajian menunjukkan bahwa kecerdasan emosional memiliki pengaruh terhadap stress akademik mahasiswa. Mahasiswa dengan kecerdasan emosional yang tinggi cenderung mampu mengelola tekanan akademik dengan lebih baik sehingga tingkat stress akademik yang dialami menjadi lebih rendah.